MATHEMATICAL MODELING OF PRODUCTION PROCESS DELAYS - T. I. Chepeleva; A. N. Chepelev (Наука и техника)
Investigation of mathematic models and problems pertaining to optimum organization of parallel production processes has been carried out with the help of a set theory, schedules, a combinatory optimization. The required and sufficient condition of efficient production system existence has been obtained in the paper. The paper considers problems concerning modeling and algorithm presentation of parallel execution of a great number of interacting and competing production processes.